TRANSFORMASI DIGITAL SEBAGAI BAGIAN DARI STRATEGI PEMASARAN DI RUMAH SAKIT SILOAM PALANGKA RAYA TAHUN 2020 - Budiyatno, Kevin Chrisanta (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2022)
Digital transformation in healthcare is implemented through a technology-based approach to improve patient-centered care. In relation to marketing strategic planning, digital transformation is included within the marketing mix of product, promotion, and place. Assessment of healthcare technology development can be based on seven major areas, which are 1) Integrated management of information technology in health; 2) Medical images; 3) Electronic Medical Record; 4) Information technology and portable devices in health; 5) Access to e-Health; 6) Telemedicine; and 7) Privacy of medical data. Digital transformation in Siloam Hospitals Palangka Raya has shown to improve cost efficiency and work process flow, although its adoption rate is not satisfactory enough. This is related to the understanding of society regarding technology. However, digital transformation can be used as part of marketing strategy to increase hospital visits.